2022
DOI: 10.1007/s00429-022-02518-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of regions of interest on tractography virtual dissection protocols: general principles to learn and to follow

Abstract: Efficient communication across fields of research is challenging, especially when they are at opposite ends of the physical and digital spectrum. Neuroanatomy and neuroimaging may seem close to each other, but the terminology and processes to study the brain can be very different. More specifically, investigations of white matter anatomy are susceptible to this challenge. This gap creates disagreement on ways to define the same underlying anatomy. Even when trying to isolate the same structure, according to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…While manual segmentation of tracts or virtual dissection methods were not a focus of this survey, multiple approaches have been proposed in the last decade that conduct fiber selection and anatomical labeling using expert knowledge ( Rheault et al, 2020 , 2022a , b ; Ille et al, 2021 ). These methods focus on improving the design of white matter dissection protocols to build more generalizable and reproducible methods.…”
Section: Discussionmentioning
confidence: 99%
“…While manual segmentation of tracts or virtual dissection methods were not a focus of this survey, multiple approaches have been proposed in the last decade that conduct fiber selection and anatomical labeling using expert knowledge ( Rheault et al, 2020 , 2022a , b ; Ille et al, 2021 ). These methods focus on improving the design of white matter dissection protocols to build more generalizable and reproducible methods.…”
Section: Discussionmentioning
confidence: 99%
“…the size and position of regions-of-interest used to extract DTI metrics, how they were drawn, etc.) which is important because recent work has shown that subtle variability in the size and position of regions of interest have downstream effects on DTI metrics 10 . Some readers may decry our decision to meta-analyse statistically heterogeneous data, but this was done purposively because forest plots provide an important graphical representation of measurement variation in relation to experimental conditions (e.g., b-values and N D ) and they summarise a large amount of information in an easy-to-interpret format.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the volumetric overlap and density metrics DSC and density correlation, we measured the volumetric bundle adjacency as defined in Schilling et al ( 2021 ). However, to avoid confusion with the streamline‐based bundle adjacency (Garyfallidis et al, 2012 ; Radwan et al, 2022 ; Rheault et al, 2022 ) metric previously defined in Garyfallidis et al ( 2012 ), and to give more intuitive meaning to the obtained values, we will refer to it as bundle distance BD. It is computed by taking the mean of minimum distances from every non‐overlapping voxel, in each segmentation, to the closest voxel in the other segmentation (Figure 3 ).…”
Section: Methodsmentioning
confidence: 99%